2009
DOI: 10.1523/jneurosci.4111-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1and A2AReceptors in Mouse Prefrontal Cortex Modulate Acetylcholine Release and Behavioral Arousal

Abstract: During prolonged intervals of wakefulness brain adenosine levels rise within the basal forebrain and cortex. The view that adenosine promotes sleep is supported by the corollary that N-methylated xanthines such as caffeine increase brain and behavioral arousal by blocking adenosine receptors. The four subtypes of adenosine receptors are distributed heterogeneously throughout the brain, yet the neurotransmitter systems and brain regions through which adenosine receptor blockade causes arousal are incompletely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 59 publications
(43 reference statements)
6
115
1
1
Order By: Relevance
“…Previous studies have shown that adenosine, through its action on A 1 receptors, inhibits the discharge of BF wakeactive neurons, reduces acetylcholine release in the cortex, and directly inhibits cholinergic MCPO/SI neurons (Alam et al 1999;Arrigoni et al 2006;Materi et al 2000;Thakkar et al 2003a;Van Dort et al 2009). In this study, we demonstrate that adenosine reduces the excitatory drive to BF cholinergic neurons, a finding that provides an additional putative inhibitory mechanism for adenosine on BF cholinergic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that adenosine, through its action on A 1 receptors, inhibits the discharge of BF wakeactive neurons, reduces acetylcholine release in the cortex, and directly inhibits cholinergic MCPO/SI neurons (Alam et al 1999;Arrigoni et al 2006;Materi et al 2000;Thakkar et al 2003a;Van Dort et al 2009). In this study, we demonstrate that adenosine reduces the excitatory drive to BF cholinergic neurons, a finding that provides an additional putative inhibitory mechanism for adenosine on BF cholinergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is a purine nucleoside; it is a by-product of ATP hydrolysis and might represent a cellular signal for energy demand in the brain (Benington and Heller 1995;Chagoya de Sanchez et al 1993). Adenosine has been shown to promote slow-wave sleep and rapid eye movement (REM) sleep in cats and rats (Basheer et al 2004;PorkkaHeiskanen et al 2002;Radulovacki 1995;Radulovacki et al 1984) and more recently in mice (Coleman et al 2006;Oishi et al 2008;Urade et al 2003;Van Dort et al 2009). In the early 1990s it was hypothesized that adenosine accumulates in the extracellular space during waking where, on reaching sufficiently high extracellular levels, it could produce sleep through inhibition of wake-active neurons, in particular those of the basal forebrain (BF) (Rainnie et al 1994).…”
mentioning
confidence: 99%
“…A variety of experimental approaches have been used to study the neural circuits that underlie anesthetic-induced unconsciousness and recovery of consciousness in rodents, including designer receptors exclusively activated by designer drugs (DREADDs) (35), genetic manipulations (36), local and systemic drug administration (10,(37)(38)(39), microdialysis (40,41), targeted brain lesions (42,43), and electrical stimulation (34). Optogenetics is a novel tool that provides distinct advantages over previous techniques used to study anesthetic-induced unconsciousness and recovery of consciousness in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Second, tracazolate levels at its AD 50 value are associated with 270% enhancement of ␣ 1 ␤ 1 ␥ 2 GABA A Rs, which may result from its opposing action mediated by adenosine A 1 and A 2 receptors (Daly et al, 1988). Tracazolate is an antagonist of adenosine A 1 and A 2 receptors, with micromolar potency where it is predicted to promote arousal and wakefulness (Van Dort et al, 2009). Therefore, greater stimulation of ␣ 1 ␤ 1 ␥ 2 GABA A Rs by tracazolate would be required for physiological antagonism of its actions at these adenosine receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%